THE RELATIONSHIP BETWEEN THE PROMOTION MIX AND THE COMPANY'S BRAND IDENTITY WITH CUSTOMER SATISFACTION AT PT. INO WANGSA BINJAI - Budi; Ivan Benedict Tambunan (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
This study aims to deepen the understanding of the contribution of promotion and branding to increasing customer satisfaction at PT. Ino Wangsa Binjai. The study used primary data with a population of 300 buyers, and 75 respondents were selected as samples through calculations using the Slovin formula. The analysis techniques applied were quantitative, including validity tests, reliability, classical assumptions, simple linear regression, and hypothesis testing through t-tests and coefficients of determination (R²). Based on the analysis results, the promotional mix variable (E_Prmsi) obtained a t-count value of -1.824 with a significance level of 0.072 (> 0.05), while the t-table was 1.99346. Because the t-count is smaller than the t-table, it can be concluded that the promotional mix does not have a significant effect on customer satisfaction. In addition, a negative t-value indicates that the direction of the relationship between the promotional mix and customer satisfaction is not in line. Conversely, the partial test shows that the company's brand variable has a significant effect on customer satisfaction with a significance value of 0.00 (< 0.05). Therefore, the first hypothesis (H1) is declared accepted. From the results of the determination coefficient test, the R Square value is 0.495, which indicates that 49.5% of changes in customer satisfaction can be explained by the company's promotional mix and brand factors, while the remaining 50.5% is influenced by other variables not examined in this study. As a recommendation, the management of PT. Ino Wangsa Binjai, especially the branch manager, is advised to implement a more cost-effective, efficient, and targeted promotional strategy, as well as utilizing social media such as Facebook, Instagram, Twitter, and print media such as newspapers to convey promotional information more effectively.